PISA Oriented Mathematics Literacy Reviewed from Self-Efficacy of Learners Taught by CORE Learning Model Assisted by Scaffolding Technique - Khasan, Nur; Kartono, Kartono; Junaedi, Iwan (Unnes Journal of Mathematics Education Research, 2021)
This research aims to find the PISA oriented mathematics literacy pattern of learners reviewed from the Insan Mulia JHS learners' self-efficacy with CORE learning model assisted by scaffolding technique. This research applied concurrent embedded design. The population consisted of seventh graders of Insan Mulia JHS Pati. The data were collected quantitatively and qualitatively. The findings showed that high-self-efficacy learner category had PISA oriented mathematics literacy patterns: mastering most of the indicators excellently except on representation indicator. The moderate-self-efficacy learners had three PISA oriented mathematics literacy patterns: averagely mastering the indicators of using mathematics tools, reasoning and arguing, and devising strategy to solve problems The low-self-efficacy learners had two PISA oriented mathematics literacy patterns: averagely mastering the indicators of communicating, representing, using mathematics tools, and reasoning and arguing; or reasoning and arguing, representing, using mathematics tools, and devising strategies to solve problems.